2015
DOI: 10.1007/s11356-015-4967-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced rice production but greatly reduced carbon emission following biochar amendment in a metal-polluted rice paddy

Abstract: Soil amendment of biochar (BSA) had been shown effective for mitigating greenhouse gas (GHG) emission and alleviating metal stress to plants and microbes in soil. It has not yet been addressed if biochar exerts synergy effects on crop production, GHG emission, and microbial activity in metal-polluted soils. In a field experiment, biochar was amended at sequential rates at 0, 10, 20, and 40 t ha(-1), respectively, in a cadmium- and lead-contaminated rice paddy from the Tai lake Plain, China, before rice croppin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Faleye et al (2013) concluded that agricultural inputs significantly increase agricultural production and provide food to the region. Zhang et al (2015) suggested that it is necessary to increase grain yield by using the potential of biochar, and reducing CO 2 emission by metal polluted rice paddies. Energy consumption needs effective planning to increase agriculture production especially rice production in a country.…”
Section: Resultsmentioning
confidence: 99%
“…Faleye et al (2013) concluded that agricultural inputs significantly increase agricultural production and provide food to the region. Zhang et al (2015) suggested that it is necessary to increase grain yield by using the potential of biochar, and reducing CO 2 emission by metal polluted rice paddies. Energy consumption needs effective planning to increase agriculture production especially rice production in a country.…”
Section: Resultsmentioning
confidence: 99%
“…The inconsistent effect of biochar amendment on N 2 O emissions might be explained by the soil properties ( Cayuela et al, 2014 ). The above mentioned studies attributed the reduced N 2 O emissions in the paddy fields with biochar amendment to soil aeration improvement after biochar application and the decrease of availability due to the absorption by biochar ( Lehmann et al, 2006 ; Zhang et al, 2010 ). These reasons could well explain the decreasing trend of N 2 O emissions in biochar treatment in the BH soil in this study, but not for the TY soil with a converse trend.…”
Section: Discussionmentioning
confidence: 99%
“…Biochar, a carbon sequestrating and recalcitrant material, is produced by the pyrolysis of plant residues under a zero or limited oxygen condition ( Cao et al, 2011 ), possessing the characteristics of a high pH, high cation exchange capacity (CEC), and a high hydrophilic characteristic, large porosity and surface area ( Lehmann et al, 2011 ). Biochar has been applied to soil as an optional amendment to improve soil fertility and grain yields via the promotion of nutrient turnover ( Zhang et al, 2010 ; Kang et al, 2016 ). Soil with a low fertility or pH value can be improved with biochar amendment ( Bakar et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, biochar alters microbial activity and abundance, thereby affecting arbuscular mycorrhizal fungi and GHG emissions. In a field experiment, increasing the biochar application rate from 0 to 10 t ha −1 , 20 t ha −1 , and 40 t ha −1 reduced N 2 O emissions from Cd‐ and Pb‐contaminated soils by 7.1%, 30.7%, and 48.6%, respectively, and increased rice yield by 10.0%, 25.1%, and 26.3% respectively (Zhang et al, 2015). The application rate of biochar was positively correlated with the suppression of N 2 O emissions, which was consistent with the results of meta‐analysis.…”
Section: Effect Of Biochar On Ghg Emissions From Various Environmentsmentioning
confidence: 99%